Comparative perspective of various shear deformation theories with experimental verification for modal analysis of hybrid laminates. (May 2017) - Biswas, Dhiraj; Ray, Chaitali
The present paper deals with the free vibration modal analysis of hybrid laminates using a finite element model based on the third order shear deformation theory (TSDT) and the first order shear deformation theory (FSDT). A computer code has been developed using MATLAB, 2013. The experimental investigation on the free vibration of hybrid laminates made of carbon and glass fibres has been conducted. The hybrid laminate is prepared by placing carbon fibres in the outermost laminae and glass fibres in the rest of the laminate. The bi-directional glass and carbon fabrics and the epoxy resin are used for the preparation of laminates in the laboratory. The experimental models of laminates have been prepared by the resin infusion process using vacuum bagging technique. The natural frequencies of hybrid laminates for different modes are determined and the mode shapes are plotted for the corresponding frequencies by experiment and numerical procedure. The finite element formulations based on TSDT and FSDT for the composite laminates predict the natural frequencies and are validated by comparing with the experimental results.